(untitled) - Kerdel, Francisco A. (New York, 2003)
This useful quick-reference presents all of the key concepts physicians and residents need to know for board certification, re-certification, and general review. Provides a quick synopsis of the most important skin conditions for non-dermatologists. Detailed table of contents and a consistent bulleted format allows instant information retrieval. Coverage includes epidemiology, pathophysiology, clinical features, diagnosis, and treatment.
Keywords: Dermatology,Skin; Diseases